Validity and reliability of a new incremental step test for people with chronic obstructive pulmonary disease - Vilarinho, Rui (2022)
Incremental step tests (IST) can be used to assess exercise capacity in people with chronic obstructive pulmonary disease (COPD). The development of a new step test based on the characteristics of the incremental shuttle walk test (ISWT) is an important study to explore. We aimed to develop a new IST based on the ISWT in people with COPD, and assess its validity (construct validity) and reliability, according to Consensus-based Standards for the selection of health status Measurement Instruments (COSMIN) recommendations. A cross-sectional study was conducted in participants recruited from hospitals/clinics. During the recruitment, the participants who presented a 6-minute walk test (6MWT) report in the previous month were also identified and the respective data was collected. Subsequently, participants attended two sessions at their homes. IST was conducted on the first visit, along with the 1 min sit-to-stand (1MSTS) test. IST was repeated on a second visit, performed 5–7 days after the first one. Spearman’s correlations were used for construct validity, by comparing the IST with the 6MWT and the 1MSTS. Intraclass correlation coefficient (ICC2,1), SE of measurement (SEM) and minimal detectable change at 95% CI (MDC95) were used for reliability. The learning effect was explored with the Wilcoxon signed-rank test. 50 participants (70.8±7.5 years) were enrolled. IST was significant and moderate correlated with the 6MWT (ρ=0.50, p=0.020), and with the 1MSTS (ρ=0.46, p=0.001). IST presented an ICC2,1=0.96, SEM=10.1 (16.6%) and MDC95=27.9 (45.8%) for the number of steps. There was a statistically significant difference between the two attempts of the IST (p=0.030). Despite the significant and moderate correlations with the 6MWT and 1MSTS, the inability to full compliance with the COSMIN recommendations does not yet allow the IST to be considered valid in people with COPD. On the other hand, the IST is a reliable test based on its high ICC, but a learning effect and an ‘indeterminate’ measurement error were shown.